ChemInform Abstract: Novel 4‐Trifluoromethylthiazole‐5‐carboxylic Acid as Acceptor in Photosensitized Dyes. Issue 20 (25th April 2013) - Iwata, Satoru; Aoyama, Misa; Uchida, Satoshi; Tanaka, Kiyoshi
Abstract synthesis and characterization